Determination of bioactive properties of Capparis spinosa fruits and use in production of Tulum cheese - Dinçoğlu, Ahmet Hulusi; Ileri, Ali; Rugji, Jerina (Emirates Journal of Food and Agriculture, 2023)
The focus of the present study was to evaluate the bioactive properties of Capparis spinosa (caper) fruits and to investigate some quality parameters of Tulum cheese with addition of caper. Analyses for the phytochemical components of caper fruit used in the production of Tulum cheese showed that it has high levels of bioactive components in terms of antioxidant activity, total phenolics, and flavonoids. It was determined that C. spinosa, which is used in the production of Tulum cheese, had a good radical scavenging activity (DPPH radical assay). Four experimental groups were arranged in the present study and analyzed on the 1, 30, 45, 60, and 90th day of ripening. T_C was designed as the control group, T_C1, T_C2, and T_C4 groups contained 1, 2, and 4% of caper. According to the obtained results as the content of caper increased, dry matter ratios, ash, pH values, tyrosine and free fatty acid values in cheese increased significantly. The microbiological evaluation revealed that the caper affected positively Lactobacillus spp. counts. The highest aroma and taste scores among caper cheeses were given to the control group (T_C). Generally, caper did not have a negative effect on the textural profile of the product. These results revealed that C. spinosa contributes to the improvement of the bioactive potential as well as increasing the quality parameters of cheese. Keywords: Caper; Bioactive properties; Functional dairy; Microbiological properties; Tulum cheese